Electrostatic-free piezoresponse force microscopy - Kim, Sungho (Sci Rep, 2017)
Contact and non-contact based atomic force microscopy (AFM) approaches have been extensively utilized to explore various nanoscale surface properties. In most AFM-based measurements, a concurrent electrostatic effect between the AFM tip/cantilever and sample surface can occur. This electrostatic effect often hinders accurate measurements. Thus, it is very important to quantify as well as remove the impact of the electrostatic effect on AFM-based measurements. In this study, we examine the impact of the electrostatic effect on the electromechanical (EM) response in piezoresponse force microscopy as a model AFM mode. We quantitatively studied the effects of increasing the external electric field and reducing the spring constant of a cantilever. Further, we explored ways to minimize the electrostatic effect. The results provide broad guidelines for quantitatively analyzing the EM response as well as, eventually, for obtaining the electrostatic-free EM response. The conclusions can be applied to other AFM-based measurements that are subject to a strong electrostatic effect between the AFM tip/cantilever and sample surface, regardless of contact and non-contact modes.